Expression of Neuropeptide FF Defines a Population of Excitatory Interneurons in the Superficial Dorsal Horn of the Mouse Spinal Cord that Respond to Noxious and Pruritic Stimuli. (15th September 2019) - Gutierrez-Mecinas, Maria; Bell, Andrew; Polgár, Erika; Watanabe, Masahiko; Todd, Andrew J.
Abstract: The great majority of neurons in the superficial dorsal horn of the spinal cord are excitatory interneurons, and these are required for the normal perception of pain and itch. We have previously identified 5 largely non-overlapping populations among these cells, based on the expression of four different neuropeptides (cholecystokinin, neurotensin, neurokinin B and substance P) and of green fluorescent protein driven by the promoter for gastrin-releasing peptide (GRP) in a transgenic mouse line. Another peptide (neuropeptide FF, NPFF) has been identified among the excitatory neurons, and here we have used an antibody against the NPFF precursor (pro-NPFF) and a probe that recognises Npff mRNA to identify and characterise these cells. We show that they are all excitatory interneurons, and are separate from the five populations listed above, accounting for ~ 6% of the excitatory neurons in laminae I-II. By examining phosphorylation of extracellular signal-regulated kinases, we show that the NPFF cells can respond to different types of noxious and pruritic stimulus. Ablation of somatostatin-expressing dorsal horn neurons has been shown to result in a dramatic reduction in mechanical pain sensitivity, while somatostatin released from these neurons is thought to contribute to itch. Since the great majority of the NPFF cells co-expressed somatostatin, these cells may play a role in the perception of pain and itch. Highlights: NPFF is expressed by around 6% of the excitatory interneurons in the superficial dorsal horn of the mouse spinal cord. NPFF cells differ from those that express substance P, cholecystokinin, neurotensin or neurokinin B. Although some NPFF cells express gastrin-releasing peptide (GRP), they do not express GFP in a GRP-GFP mouse line. Some NPFF cells are activated by noxious or pruritic stimuli.